Mosques as Community-Based Educational Institutions: A Prophetic Social Science Perspective on Sakinah Family Education in Urban Indonesia - Katni Katni; Nurul Iman; Noor Amirudin; Hilma Rofi Mahfudzhah; Hilal Chamdi (STAI Hubbulwathan Duri, 2026)
The movement to promote sakinah (harmonious) families in Indonesia has been implemented for more than two decades; however, its outcomes remain limited, as reflected in the persistently high rates of divorce and domestic violence. Institutions such as BP4 have not yet played an optimal role, and public participation in harmonious family programs remains relatively low. In addition, formal educational institutions have not fully accommodated family education, leading to the emergence of mosque-based family education initiatives. This study investigates the role of mosques in providing harmonious family education using a prophetic social science approach.This research employed a qualitative field research design. The study was conducted in three mosques in the urban area of Ponorogo: Baitul Mukhlisin Mosque, Nurul Hasan Mosque, and Al Manar Mosque. Research subjects included mosque administrators and congregants, supported by documentary analysis. Data were collected through in-depth interviews, observation, and documentation, and analyzed both during and after fieldwork. Data validity was ensured through triangulation techniques.The findings indicate that mosques play a significant role in harmonious family education through three main dimensions: (1) a religious role, which strengthens spiritual and moral foundations of family life; (2) a humanization role, which fosters social awareness, mutual respect, and ethical family relations; and (3) an independence role, which empowers families through knowledge and social support networks.These findings demonstrate that mosques function as important social capital in urban communities. Mosque-based harmonious family education offers a strategic approach to addressing rising divorce rates, domestic violence, bullying, and socio-economic challenges such as poverty and unemployment within families.